The railway rapid transit network construction scheduling problem. (December 2019) - Canca, David; De-Los-Santos, Alicia; Laporte, Gilbert; Mesa, Juan A.
Highlights: We model the network construction Project as a QIP problem. The model corresponds to a Resource-constrained project scheduling problem. Revenues and costs are both dependent on the schedule. We solve the model by a Branch-and-Cut procedure. We illustrate the methodology with the construction of the Metro of Seville. Abstract: We consider the problem of scheduling the construction of a railway rapid transit transportation network. We assume that the network topology is already known. The problem consists of sequencing the construction tasks in order to maximize the long term profit of the project. The problem can be viewed as a resource-constrained project scheduling problem, where both the budget and available construction equipment act as resources influencing the schedule. Since lines segments can be put into operation as soon as they are finished, both the costs and the revenues are dependent on the schedule. We propose a quadratic integer programming model which is solved to optimality by branch-and-cut. To illustrate the methodology we apply the model to the construction of the Metro network of the city of Seville, and we perform sensitivity analyses on several model parameters.